2000
DOI: 10.1021/la9909446
|View full text |Cite
|
Sign up to set email alerts
|

Properties of AOT Aqueous and Nonaqueous Microemulsions Sensed by Optical Molecular Probes

Abstract: Nonaqueous microemulsions of AOT in n-hexane and n-heptane by using six polar solvents as water substitutes such as glycerol (GY), ethylene glycol (EG), propylene glycol (PG), formamide (FA), dimethylformamide (DMF), and dimethylacetamide (DMA) were studied and compared with the corresponding aqueous reverse micelles. The microenvironment generated by these systems was sensed by following the solvatochromic behavior of 1-methyl-8-oxyquinolinium betaine (QB). By varying Ws (Ws ) [polar solvent]/[AOT]), the exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
128
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(139 citation statements)
references
References 35 publications
11
128
0
Order By: Relevance
“…Moreover, it was shown that the micropolarity of the AOT reverse micelle interface was greater than that corresponding to the bulk DMF and DMA. 33 These facts explain satisfactorily the high values for the K b values obtained and confirm that the sulfonate group was "bare" in these reverse micelles and consequently more able to hydrogen bond to the solute.…”
supporting
confidence: 68%
“…Moreover, it was shown that the micropolarity of the AOT reverse micelle interface was greater than that corresponding to the bulk DMF and DMA. 33 These facts explain satisfactorily the high values for the K b values obtained and confirm that the sulfonate group was "bare" in these reverse micelles and consequently more able to hydrogen bond to the solute.…”
supporting
confidence: 68%
“…The microemulsions can be characterized by using molecular probes such as: 1-methyl-8-oxyquinolinium betaine (QB) or the free base of the dye acridine orange AO [2]. The aim of the present contribution is to investigate the properties of the base AO in aqueous and nonaqueous AOT/n-heptane microemulsions.…”
Section: Introductionmentioning
confidence: 99%
“…o-Nitroaniline (o-NA) is a very convenient molecular probe because the binding constants to the micelle can be determined by UVvisible spectroscopy. 7,8 The goal of the proposed work was to study the influence of different kosmotropic and chaotropic additives introduced in the water pockets of reverse micelles on both the chromatographic retention factor of model compounds and binding of a molecular probe to reverse micelles, by using reverse microemulsion chromatography and ultravioletvisible spectroscopy.High-performance liquid chromatographic (HPLC) analyses were carried out with a microcolumn liquid chromatograph "Milichrom-4" (Nauchpribor, Oryol, Russia) equipped with an isocratic pump and a variable-wavelength UV detector. The detection of compounds was carried out at ambient temperature.…”
mentioning
confidence: 99%
“…o-Nitroaniline (o-NA) is a very convenient molecular probe because the binding constants to the micelle can be determined by UVvisible spectroscopy. 7,8 The goal of the proposed work was to study the influence of different kosmotropic and chaotropic additives introduced in the water pockets of reverse micelles on both the chromatographic retention factor of model compounds and binding of a molecular probe to reverse micelles, by using reverse microemulsion chromatography and ultravioletvisible spectroscopy.…”
mentioning
confidence: 99%